CdS Covered with Ga-P Electron Exchange Membrane for Efficient Photocatalytic Hydrogen Prodection (Journal of Solar Energy Research Updates, 2025)
Abstract: CdS is one of the best semiconductor photocatalysts. However, photocorrosion will occur when CdS takes part in the photocatalytic system. The general solution is to add sacrificial reagents to inhibit this phenomenon. Even so, it can not maintain the stability of CdS. In order to improve the stability and efficiency of CdS in pure water, Ga-P electron exchange membrane was designed to modify its surface. Under radiation of visible light, a significant increase can be observed in hydrogen production activity. In the absence of Pt as electron transfer agent, the modification of Ga-P realizes decomposition of pure water from zero to one. At the same time, the hydrogen production rate is increased about 5 times with Pt and catalytic life is greatly extended. Through proof of controlled experiment, Ga-P electron exchange membrane can not only prolong the lifetime of photogenerated electrons, but also change the direction of electrons. The formation of a protective membrane makes composite photocatalyst improve the stability and enhance the photocatalytic activity. Based on the analysis of TEM, fluorescence lifetime, UV-Vis diffuse reflection and photocurrent response, the mechanism is analyzed from atomic radius, nuclear orbit and energy level. For homogeneous electronic band structure and XPS analysis, we determined that the binary catalyst formed an S-scheme heterojunction. The work provides a potential way to design a more efficient and stable composite photocatalyst in the future. And contributed to the development of S-scheme heterojunctions.